2017
DOI: 10.1177/1464884916689573
|View full text |Cite
|
Sign up to set email alerts
|

Post-industrial fog: Reconsidering innovation in visions of journalism’s future

Abstract: As US news organizations have faced twin crises in funding and authority in recent years, innovation has become a key concept and ideal driving many interventions aimed at saving journalism. Often, ahistorically and uncritically deployed notions of innovation elide questions of digital journalism’s democratic aspirations in favor of market-oriented solutions. To critically examine the discourse around innovation, this article interrogates documents produced by think tanks and non-profit institutes researching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 44 publications
1
24
0
4
Order By: Relevance
“…This could potentially harm innovation, as managers who lack the time to conduct information searches and re-evaluation will use their existing cognitive schemas instead of new stimuli (Shaw, 1990). In line with these arguments, we found that managers who do not have time for skill develop-our sample are naturally partial to the institutionalized ideals prevalent inside their industry; yet, at the same time, as also pointed out by Creech and Nadler (2018), they appear to be influenced by the positive ideals surrounding innovation, new technology, and change.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This could potentially harm innovation, as managers who lack the time to conduct information searches and re-evaluation will use their existing cognitive schemas instead of new stimuli (Shaw, 1990). In line with these arguments, we found that managers who do not have time for skill develop-our sample are naturally partial to the institutionalized ideals prevalent inside their industry; yet, at the same time, as also pointed out by Creech and Nadler (2018), they appear to be influenced by the positive ideals surrounding innovation, new technology, and change.…”
Section: Discussionsupporting
confidence: 81%
“…In fact, innovation has been a promoted ideal, as suggested by Chreech and Nadler (2018). In reports created by think tanks and non-profit institutes targeting the media industry, Chreech and Nadler (2018) detect a possible pro-innovation bias (Rogers, 2003), as the concept of innovation is pictured as the only route out of the current media industry crisis (Creech & Nadler, 2018). Creech and Nadler (2018) argue that these reports function as innovation advocacy during a time when members seem to have spent their entire career in the media industry, as almost 40% stated that they have been working in the media industry for more than 25 years.…”
Section: Methodsmentioning
confidence: 99%
“…The path of innovation adoption regarding 360° videos in news organizations consists of three major steps: the awareness, the experimentation, and the Lajqi, Lischka, Normative principles in newsroom innovation as professional values by the interviewed knowledge champions, which indicates that the constant-innovation narrative (Russell, 2017) is adopted in journalism. In contrast to Creech and Nadler's (2017) assumption that the focus on innovation marginalizes normative standards, this study finds that innovations are carefully evaluated against professional norms, especially when these norms are regarded as strategically important. Moreover, normative principles relating to digital journalism do not collide with but enhance innovation adoption.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, normative principles relating to digital journalism do not collide with but enhance innovation adoption. However, seeing that traditional norms and role conceptions are extended with novel norms in the digital age, which may be enhanced through innovations, Creech and Nadler's (2017) concern remains valid.…”
Section: Discussionmentioning
confidence: 99%
“…Journalists within news organizations actively advocate pursuing such entrepreneurial approaches to newswork (Vos & Singer, 2016). Newspapers that vocally champion innovation also attract industry acclaim and accolades, as well as attention from the philanthropic community, which can iteratively generate more capital for the business (Creech & Nadler, 2018). In this bewildering quest to integrate new revenue streams into day-to-day practice, newspaper executives have reported feeling paramount pressure to be first-to-market with innovative ideas (Sylvie, 2018).…”
Section: News Investment As a Value Propositionmentioning
confidence: 99%